PENGARUH MEDIA DIORAMA TERHADAP HASIL BELAJAR IPAS MATERI KEANEKARAGAMAN HAYATI SISWA KELAS IV SDN 231 PALEMBANG - Yudha, Imam Khatami; Hakim, Lukman; Mahendra, Agung (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of using dioramas on the learning outcomes of fourth-grade students in the biodiversity science subject at SDN 231 Palembang. This research was motivated by the low learning outcomes of students, which are still below the Learning Objective Achievement Criteria (KKTP), necessitating the need for engaging and concrete learning media to help students understand the material. This study used a quantitative approach with a quasi-experimental research type and a nonequivalent control group design. The sample consisted of students in grade IV.A as the control class and grade IV.B as the experimental class. Data collection was conducted through pretests and posttests. Data were analyzed using normality tests, homogeneity tests, independent sample t-tests, and the N-Gain test. The results showed a significance value of 0.002 < 0.05, indicating that the use of dioramas on student learning outcomes was significant. The N-Gain test results indicated that the improvement in learning outcomes in the experimental class was 47.20%, categorized as moderate, while in the control class it was 18.58%, categorized as low. Thus, it can be concluded that the use of diorama media has a significant effect on the learning outcomes of fourth-grade students at SDN 231 Palembang in the science and science subject of biodiversity. This is indicated by an increase in the average student score from 61.88 in the pretest to 76.67 in the posttest after the application of diorama media. Keywords: diorama media 1, learning outcomes 2, IPAS 3, biodiversity 4.